2015
DOI: 10.1111/1752-1688.12308
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Streamflow and Water Quality Sensitivity to Climate Change and Urban Development in 20 U.S. Watersheds

Abstract: Watershed modeling in 20 large, United States (U.S.) watersheds addresses gaps in our knowledge of streamflow, nutrient (nitrogen and phosphorus), and sediment loading sensitivity to mid-21st Century climate change and urban/residential development scenarios. Use of a consistent methodology facilitates regional scale comparisons across the study watersheds. Simulations use the Soil and Water Assessment Tool. Climate change scenarios are from the North American Regional Climate Change Assessment Program dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 52 publications
4
57
1
Order By: Relevance
“…Verma et al () projected a reduction in flow of 8.5%, which would be in the lowest quartile of our results. The sediment results from these studies are similar to those projected for streamflows, with Johnson et al () projecting very small (0.6%) increases in total suspended solids, Bosch et al () projecting larger increases of 8–32%, and Verma et al () projecting decreases of 10.4%. With the exception of the high estimate of 32% from Bosch et al () these estimates are within the range of our results, with the results from Johnson et al () being closest to our median.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Verma et al () projected a reduction in flow of 8.5%, which would be in the lowest quartile of our results. The sediment results from these studies are similar to those projected for streamflows, with Johnson et al () projecting very small (0.6%) increases in total suspended solids, Bosch et al () projecting larger increases of 8–32%, and Verma et al () projecting decreases of 10.4%. With the exception of the high estimate of 32% from Bosch et al () these estimates are within the range of our results, with the results from Johnson et al () being closest to our median.…”
Section: Resultssupporting
confidence: 71%
“…Several other studies have examined climate change in the Maumee River, although they used the CMIP3 climate scenarios and had differences in methodologies and study periods. Results from both Johnson et al () and Cherkauer and Sinha () suggested little change in the average flows by Mid‐Century, whereas Bosch et al () projected a 6–18% increase in flow; these results are within the middle two quartiles of those presented here. Verma et al () projected a reduction in flow of 8.5%, which would be in the lowest quartile of our results.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Modeling studies applying similar methods to watersheds across the nation generally project increases in total nutrient loads (median) for much of the eastern and northern U.S. (Johnson et al. ; Fant et al. ; Sinha et al.…”
Section: Resultsmentioning
confidence: 99%
“…Agricultural productivity and water resources can be degraded with unfavorable sequences from these weather events, resulting in: substantial losses of soil, nutrients, and fertilizers in agricultural fields; pollutant loadings to waterbodies; and subsequent water quality issues, particularly in agriculturally dominated regions (Whitehead et al 2009;Johnson et al 2015). The National Climate Assessment (2014) concluded that climate change "is already affecting the American people in far-reaching ways" and that the future will be unlike the past.…”
mentioning
confidence: 99%